Implementasi Kebijakan Restrukturisasi Birokrasi Dalam Pengembangan Good Governance (Suatu Studi di Dinas Kependudukan dan Pencatatan Sipil Kota Manado) - Arson, Yurivo; Kiyai, Burhanuddin; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: In this research, the connection of the restructuring of regional organizations in particularly the establishment of organizations in local government bureaucracy, the efficiency will be seen from the efficient of using public funds (budget) for the purposes of the bureaucracy and its efficiency of public services. This concept will be seen by the following indicators: the ability to simplify organizational / bureaucratic areas, which is including type of organization, the number of organizations and organizational echelon, the distribution of the regional budget allocation (APBD) for the purposes of governance (the bureaucracy) and for the purposes of public (community) as well as the ability to make changes / improvements to public services. In this study, the bureaucracy is within the third perspective (Value-Free) which is means Government Organizational Bureaucracy is a set of tasks and positions that formally organized, where the implementation of the system hierarchy contains the authority and responsibility, as any unit / work unit has mutual influence and determine the implementation of the work to achieve thorganizational goals. Thus, the government bureaucracy focus on this study is the Department of Population and Civil Registration Manado.Keywords: implementation, restrukturisasi birokrasi good governance